Duration and dynamics of the best orbital analogue to the present interglacial - Giaccio, Biagio; Regattieri, Eleonora; Zanchetta, Giovanni; Nomade, Sebastien; Renne, Paul R.; Sprain, Courtney J.; Drysdale, Russell N.; Tzedakis, Polychronis C.; Messina, Paolo; Scardia, Giancarlo [UNESP]; Sposato, Andrea; Bassinot, Franck (Geological Soc Amer, Inc, 2015)
Past orbital analogues to the current interglacial, such as Marine Isotope Stage 19c (MIS 19c, ca. 800 ka), can provide reliable reference intervals for evaluating the timing and the duration of the Holocene and factors inherent in its climatic progression. Here we present the first high-resolution paleoclimatic record for MIS 19 anchored to a high-precision Ar-40/Ar-39 chronology, thus fully independent of any a priori assumptions on the orbital mechanisms underlying the climatic changes. It is based on the oxygen isotope compositions of Italian lake sediments showing orbital-to millennial-scale hydrological variability over the Mediterranean between 810 and 750 ka. Our record indicates that the MIS 19c interglacial lasted 10.8 +/- 3.7 k.y., comparable to the time elapsed since the onset of the Holocene, and that the orbital configuration at the time of the following glacial inception was very similar to the present one. By analogy, the current interglacial should be close to its end. However, greenhouse gas concentrations at the time of the MIS 19 glacial inception were significantly lower than those of the late Holocene, suggesting that the current interglacial could have already been prolonged by the progressive increase of the greenhouse gases since 8-6 ka, possibly due to early anthropogenic disturbance of vegetation.